THE IMPACT OF ONGOING PANDEMIC COVID-19 ON INDONESIAN DEMOCRACY: DEMOCRATIC BREAKDOWN, POLITICAL INEQUALITY, AND DEEPENING CLIENTELISM - Jati, Wasisto Raharjo (Jurnal Penelitian Politik, 2022)
This study aims to analyze the ongoing pandemic covid-19 that brings unprecedented consequences to the Indonesian democracy system. One prominent thing to note is that the current declining democracy seems to worsen. This condition may happen due to the restricted civil liberties and increasing use of state control on behalf of pandemic policies. While these two likely result from executive aggrandizement, the latter premise seems to be a side effect of increasing personal power because pandemic makes people dependent on state actors. The way pandemic covid-19 decreases the quality of democracy in Indonesia remains unanswered clearly. This study finds three significant consequences on Indonesia's democracy such as democratic breakdown, political inequality, and deepening clientelism. In other words, these three consequences also mean the pandemic covid 19 becomes blessing in disguise for elites to push their political agendas on behalf of pandemic policies. This study will further investigate other impacts of covid-19 on Indonesian democracy. Keywords: pandemic covid-19, Indonesian democracy, democratic breakdown, the persistence of authoritarianism, deepening clientelism